CONSENT FOR MEDICAL ACTION (INFORMED CONSENT) FOR SURGICAL ACTION AFTER THE ENFORCEMENT OF LAW NO. 17 OF 2023 CONCERNING HEALTH - Laksmi, Ni Putu Ayu Utari; I Gusti Ngurah Parikesit Widiatedja (RADJA PUBLIKA, 2026)
Health services are a form of public service aimed at improving the level of public health. In medical practice, particularly in invasive procedures such as surgical operations, medical consent or informed consent is required as a form of legal protection for both patients and medical personnel. This study aims to examine the concept, principles, and legal regulations regarding the implementation of informed consent in surgical procedures from the perspective of Law Number 17 of 2023 concerning Health. The research uses a qualitative method with a literature review approach by analyzing various relevant sources such as books, scientific journals, and legal regulations. The results show that informed consent is a communication process between medical personnel and patients that includes information about diagnosis, objectives of medical procedures, treatment processes, benefits, risks, and alternative treatments. The regulation of informed consent in Law Number 17 of 2023 concerning Health provides a clear legal basis regarding patients' rights to obtain information and give consent for medical procedures. In surgical practice, the implementation of informed consent is particularly important due to the higher level of risk associated with surgical procedures. Therefore, the proper implementation of informed consent in a clear, transparent, and lawful manner can provide balanced legal protection for both patients and medical personnel while minimizing the potential for medical disputes.